Building an Innovative Culture through Technological Leadership: An Empirical Approach - Fadjar Rizky Wahyu Ramadhan; Her Pirngadi; Marsad Marsad; Nurhidayah Nurhidayah; Ikka Kartika Abbas Fauzi (International Journal of Management and Economic Research (IJOMER), 2025)
Digital transformation in education has put schools at a critical point to adapt and innovate systemically. This study aims to describe the practice of technological leadership and its contribution to the formation of an innovative culture in an integrated Islamic school environment. Using a qualitative approach and case study design, the research was conducted at SMP IT Aqidah Bekasi through participatory observation, in-depth interviews, and documentation studies. The results show that the principal plays a central role in formulating the digital vision, building teachers' capacity, providing technological infrastructure, and creating a collaborative ecosystem that supports innovation. An innovative culture grows through teacher learning communities, student expression spaces, and the integration of Islamic values into the digitization process. However, challenges such as senior teacher resistance, limited advanced training and less than optimal documentation of innovations are still obstacles that need to be overcome. This study concludes that strategic, participatory and value-based technology leadership is an important catalyst for sustainable school culture transformation. The implications of these findings include the development of contextualized educational leadership models, as well as the formulation of structured and inclusive innovation policies.